Multimodal chemosensory integration through the maxillary palp in Drosophila. - Takashi Shiraiwa (PLoS ONE, 2008)
Drosophila melanogaster has an olfactory organ called the maxillary palp. It is smaller and numerically simpler than the antenna, and its specific role in behavior has long been unclear. Because of its proximity to the mouthparts, I explored the possibility of a role in taste behavior. Maxillary palp was tuned to mediate odor-induced taste enhancement: a sucrose solution was more appealing when simultaneously presented with the odorant 4-methylphenol. The same result was observed with other odors that stimulate other types of olfactory receptor neuron in the maxillary palp. When an antennal olfactory receptor was genetically introduced in the maxillary palp, the fly interpreted a new odor as a sweet-enhancing smell. These results all point to taste enhancement as a function of the maxillary palp. It also opens the door for studying integration of multiple senses in a model organism.